ANALISIS EFISIENSI DAN KEUNTUNGAN USAHATANI JAGUNG DI DESA WARINTA KECAMATAN PASARWAJO KABUPATEN BUTON - Muzuna, Muzuna (Media Agribisnis, 2018)
The research objectives are as follows: (1) To determine the level of efficiency in the use of seed, fertilizer and labor production factors in corn farming in Warinta Village, Pasarwajo Sub-district, Buton Regency; and (2) To find out the great benefits of corn farming in Warinta Village, Pasarwajo Sub-district, Buton Regency. The population in this study were all farmers engaged in maize in Warinta Village, Pasarwajo Sub-district, Buton Regency, amounting to 32 people because the population was less than 100 and the sample was taken by the census. To estimate the production function of maize farming, the frontier production function equation model is used as follows: Ln Y = ?0 + ?1lnX1 + ?2lnX2 + ?3lnX3 + e and to calculate the price efficiency, the production function used is: NPMX = PX or NPMX / PX = 1. The conclusions of the results of the study are: (1) Large factor prices efficiency of labor production amounted to 0.8670. There needs to be a reduction in labor outpouring factors so that efficient use of labor can be achieved; (2) The efficiency of the price of fertilizer production factor is 11.1422. It is necessary to add fertilizer production factors so that the efficiency of fertilizer use can be achieved; (3) The amount of efficiency in the price of seed production factors is 3.9604. Need for additional seed production factors so that efficient use of seedlings is achieved; and (4) The average income of a one-time hybrid corn farmer in Warinta Village, Pasarwajo District, Buton Regency is IDR 5,923,543.88 with an average total revenue of IDR 7,361,046.88 and the total cost incurred in the amount of IDR 1,437 .502.99.  Keywords: corn farming, price efficiency